Allergic rhinoconjunctivitis in elite athletes - Katelaris, C. H.; Carrozzi, F. M.; Burke, T. V. (Sports Medicine, 2003)
Allergic rhinoconjunctivitis is a common condition with a peak incidence in the age range of the majority of elite athletes. The condition has been shown to have a significant impact on the quality of life of those affected and poses particular challenges when present in the elite athlete. When an athlete is looking for exceptional performance at events such as the Olympic Games, any factor which affects quality of life by interfering with sleep, decreasing the ability to concentrate, or reducing peak physical fitness, may have a significant impact on the ability to perform at one`s best.